(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Capsaicin is a pungent highly domesticated fat soluble alkaloid having its origin from Bolvia and Brazil. It is biosynthesized via phenylpropanoid pathway and branched chain fatty acid pathway. Mostly found in trans isomeric form. Its pungent analogues are synthesized using amidation reactions catalyzed by lipases and non-pungent analogues using acyl chain lengths and different substituent in aromatic ring. It acts by binding TRPV1 and shows wide applications in relief from pain, breast and prostate cancer, obesity, heart diseases and hair loses. Its increased intake may cause lesions of liver and kidney along with gastric cancer. A review is made of capsaicin research focusing mainly on its origin, biosynthesis, chemistry and pharmacology, including its toxicological aspects.